Communication and Marketing Behaviour of Tomato Growers in Southern Odisha, India (Indian Journal of Extension Education, 2025)
The study investigated the communication and marketing behaviour of tomato growers in southern Odisha during the 2023–24 cropping season. The study employed a multi-stage random sampling technique to select 120 farmers from twelve villages in Gajapati and Rayagada districts. Data were collected using a structured interview schedule, focusing on mass media exposure, information seeking, information sharing, planning, decision making, and post-marketing review. Descriptive statistics, Pearson’s correlation and multiple regression analyses were used to analyse the data. The results revealed that 55.8 per cent of growers had medium planning ability and 64.2 per cent displayed medium overall marketing behaviour. Mobile phones and television were always used by about three quarters of respondents, while newspapers, radio, farm magazines and extension publications were seldom consulted. Extension officials and local leaders were important but infrequently contacted sources of information. Positive correlations were found between communication behaviour and marketing behaviour, and variables such as education, farm size and participation in extension activities significantly influenced both. Enhancing digital extension services, improving farmer training on market planning and expanding market infrastructure could substantially improve tomato growers’ decision-making and profitability.